Two Term Approximation for Near Field Analysis of Wire Scatterers - Vaibhav Suresh Yavalkar (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
This paper presents an analysis of near field of wire scatterers. In this paper, the exact distribution on wire scatterers is approximated using a more accurate two term approximation for the ease of closed form analysis. It has been shown that the results obtained using the two term approximation are very close to the cosinusoidal distribution for the element length up to 0.7  with less than 5% error in the field evaluated from this approximation. This analysis formulation is useful in estimating fields form wire scatterers, mutual coupling in an array of scatterers or analysis of Yagi-Uda antennas.